SEMIOTIC ANALYSIS OF COVID-19 MEME IN SOCIAL MEDIA - Sri Kurniati Almucharomah; Wening Sahayu; Sulis Triono (University of Kuningan, 2023)
The presence of social media makes the process of social interaction experience very significant changes. Communication through social media is a very important social interaction in human life. Along with the increasing use of social media, it has spawned new phenomena among social media users, one of which is creativity in making memes. Memes can be in the form of text or images that contain issues and events in a style that intrigues and are widely discussed because they spread and comment so quickly on social media. The purpose of this study was to describe the signifier and signified in the Covid-19 meme and explain the meaning contained in the Covid-19 meme. The Covid-19 meme itself is one of the memes found on social media. The approach used in this research was a qualitative approach which produces descriptive analysis. The researcher seeked the facts behind the creation of the Covid-19 meme circulating on social media. The signifiers found in the Covid-19 meme include snippets of famous movie and game scenes. The insinuations in the sentences are also reality. The sentences provide a statement that contains information and expression of the feelings of the creator as a fighter in the pandemic season.